Answering Human Resource Challenges in the Tourism Sector in the Era of Society 5.0 - Afiah Mukhtar; Masradin Masradin; Rif’ah Shafwah; Aigistina Aigistina; Ahmad Yani Abdurrahman (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2024)
The Society 5.0 era is marked by the integration of digital technology in various aspects of life, including the tourism sector. Rapid technological changes, shifting tourist trends and diverse demands from tourists require the tourism sector to adapt according to the demands of the times so that answers are needed to the challenges faced by human resources in the tourism sector in the 5.0 era. This study uses a qualitative approach with a systematic literature review method. The literature approach related to tourism HR challenges was searched comprehensively using relevant keywords in searches through various online databases. The literature selection process was carried out by considering the reputation of the journal and the recency of the publication (last 7 years) and analyzed in depth using the content analysis method. The conclusion from the research findings is that the human resource challenges in the tourism sector in the era of Society 5.0 are: employee turnover trends, developing digital skills, diversity and inclusion, adopting new technology, work-life balance and developing partnerships with educational institutions. The implication of these findings is the importance of tourism sector business actors taking strategic steps in responding to human resource challenges so that the tourism sector remains relevant to current conditions and remains competitive in the Society 5.0 era.